Pediatric Stinger Syndrome: Acute Brachial Plexopathy After Minor Trauma. Issue 11 (November 2015) - Quong, Whitney L.; Hynes, Sally L.; Arneja, Jugpal S.
Abstract : Summary: The "stinger" or "burner" is a form of transient brachial plexopathy termed for its characteristic knife-like pain extending from the neck to the fingertips. Muscle weakness and paresthesia are oftentimes associated symptoms and are similarly temporary. Commonly observed in athletes of contact sports, the stinger results from high force trauma causing either traction/direct compression to the brachial plexus or extension/compression of the cervical nerve roots. We describe a pediatric case of a stinger in a 14-year-old boy, which was caused by a relatively low force trauma accident. Our management strategy and recommendations are discussed.